Collateral Registries for Movable Assets : Does Their Introduction Spur Firms' Access to Bank Finance? - Love, Inessa; Martínez Pería, María Soledad; Singh, Sandeep (World Bank, Washington, DC, 2013)
Using firm-level surveys for up to 73 countries, this paper explores the impact of introducing collateral registries for movable assets on firms' access to bank finance. It compares firms' access to bank finance in seven countries that introduced collateral registries for movable assets against three control groups: firms in all countries that did not introduce a registry, firms in a sample of countries matched by location and income per capita to the countries that introduced registries for movable assets, and firms in countries that undertook other types of collateral reforms but did not set up registries for movable assets. Overall, the analysis finds that introducing collateral registries for movable assets increases firms' access to bank finance. There is also some evidence that this effect is larger among smaller firms.